2012
DOI: 10.1155/2012/210437
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Characterization of the HPA‐MCM‐48 Type Catalysts Produced by the Direct Hydrothermal and Room Temperature Synthesis Methods

Abstract: MCM-48 type support materials synthesized by the direct hydrothermal synthesis (HTS) and room temperature synthesis (RTS) methods were incorporated with tungstophosphoric acid (TPA) in the range of 10–40 wt% by using a wet impregnation technique in methanol solutions. Resulting HPA-MCM-48 catalysts were characterized by the XRD, Nitrogen Physisorption, SEM, TEM, EDS, and FT-IR methods in order to determine the effects of different initial synthesis conditions on the catalyst properties. RTS samples were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Experimental conditions were as follows: catalyst to oil weight ratio, 1.5%; MeOH to oil volume ratio, 2:1; temperature, 70°C; reaction time, 3h; Feed, 10g; n/a It was found that the room temperature synthesis method resulted in catalysts with higher crystallinity, higher surface area and pore volume and were more economical. (Gucbilmez et al, 2012) PTA supported on MCM 41 esterification of acetic acid with noctanol MCM 41 could take higher loadings of up to 71% but optimal values were obtained at 60% i.e. surface acidity was maximized at this loading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental conditions were as follows: catalyst to oil weight ratio, 1.5%; MeOH to oil volume ratio, 2:1; temperature, 70°C; reaction time, 3h; Feed, 10g; n/a It was found that the room temperature synthesis method resulted in catalysts with higher crystallinity, higher surface area and pore volume and were more economical. (Gucbilmez et al, 2012) PTA supported on MCM 41 esterification of acetic acid with noctanol MCM 41 could take higher loadings of up to 71% but optimal values were obtained at 60% i.e. surface acidity was maximized at this loading.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that fatty acid neutralization might be the reason for the loss in yield. Studies conducted on other mesoporous materials such as SBA-15 and MCM-41 have reported similar yield when other oils were used as feedstock (Brahmkhatri and Patel, 2011;Gucbilmez et al, 2012). 12phosphotungstic acid (PTA) impregnated on four supports namely silica, alumina, hydrous zirconia, and activated carbon were used for the production of biodiesel from low quality canola oil which contained up to 20 wt% FFA.…”
Section: Conversion and Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…[34,35] In contrast to natural molecular sieves (zeolites), the M41S structures exhibit interesting properties, such as higher surface areas (up to 1600 m 2 /g), higher pore volumes (up to 1.2 cm 3 /g), and pore sizes in the mesoporous range (2-10 nm). [36] These properties have made the M41S family structures the subject of several studies on a wide range of applications in adsorption and separation industrial processes and also in catalysis and biomedicine. [37] F I G U R E 1 Proposed pathways to obtain mono-and bicyclic terpenes from acidic isomerization of pinenes However, the most remarkable feature of this family of materials is its well-ordered pore system, composed of a uniform shape and narrow size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Heteropoly acids (HPAs) are complex proton acids that incorporate polyoxometalate anions (heteropoly anions) having metal-oxygen octahedra as the basic structural units. HPAs have several advantages such as very strong Brönsted acidities approaching the super acid region [6] and high oxidant activities in multielectron redox reactions under mild conditions. Their acid-base and redox properties can be varied widely by changing their chemical compositions.…”
Section: Introductionmentioning
confidence: 99%